Proposed improvements on performance management system at PT JIEP by using balanced scorecard - Lola Cahyana; Andika Putra Pratama; John Welly (Journal of Digital Business and Marketing, 2025)
Purpose: This study addresses the urgent need for an effective performance management system at PT JIEP to bridge the gap between current practices and a holistic approach that aligns individual objectives with the organization’s goals. This study aims to design an improved framework using the Balanced Scorecard (BSC) to enhance employee engagement, development, and strategic alignment. Research Methodology: A mixed-method approach was employed, combining quantitative surveys (n=61) and qualitative focus group discussions with the employees. The survey measured six performance management purposes and six key activities on a Likert scale. Quantitative data were analyzed using SPSS for validity and reliability, and qualitative data underwent thematic analysis. Triangulation was used to integrate both datasets. Results: The findings indicate critical deficiencies in administrative efficiency, employee development opportunities, guidance for achieving goals, frequency of evaluations, and transparency in performance consequences. Key challenges include reliance on annual KPI reviews, limited feedback, narrow reward structures and insufficient managerial coaching. Conclusions: The current system lacks strategic alignment, continuous feedback, and diverse recognition methods to improve employee performance. Implementing the BSC framework, diversifying rewards, enhancing managerial coaching skills, and establishing regular evaluations are essential for improving engagement, motivation, and alignment with strategic goals. Limitations: This study focused solely on PT JIEP, limiting its generalizability. Reliance on self-reported data may have introduced bias. Contribution: This research contributes a validated BSC-based performance management framework adaptable to similar organizational contexts, offering actionable strategies to align individual and corporate objectives while fostering a culture of continuous improvement.